2006
DOI: 10.1161/circulationaha.106.625848
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight, a Risk Factor for Cardiovascular Diseases in Later Life, Is Already Associated With Elevated Fetal Glycosylated Hemoglobin at Birth

Abstract: Background-It remains unclear whether the association between low birth weight and insulin resistance in adulthood has its origin in utero or whether it develops later in life depending on predisposition and exogenous factors. Methods and Results-Total glycosylated hemoglobin (TGH) was quantified at delivery in 1295 mother/child pairs serving as a surrogate of maternal and fetal glycemia. Multivariable regression analysis considering gestational age at delivery, the child's sex, maternal body mass index, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…To assess the clinical relevance of our unique finding that, unlike TRPM6, TRPM6(V 1393 I) and TRPM6(K 1584 E) were not stimulated by insulin, 997 women from the Berlin Birth Cohort (BBC) (13,14) were analyzed. Detailed data analysis of the entire study population including the maternal TRPM6(V 1393 I) and TRPM6 (K 1584 E) genotypes is shown in Table 1 and Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the clinical relevance of our unique finding that, unlike TRPM6, TRPM6(V 1393 I) and TRPM6(K 1584 E) were not stimulated by insulin, 997 women from the Berlin Birth Cohort (BBC) (13,14) were analyzed. Detailed data analysis of the entire study population including the maternal TRPM6(V 1393 I) and TRPM6 (K 1584 E) genotypes is shown in Table 1 and Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 997 women from the previously described Berlin Birth Cohort (BBC) (13,14) were included in the study. Mean weight and mean blood pressure were calculated every trimester.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 As the system works independently of the haemoglobin type, it allowed quantifying glycosylation of fetal haemoglobin (HbF) as well as adult haemoglobin. Briefly, glycated haemoglobin was separated from non-glycated haemoglobin by boronate affinity chromatography.…”
Section: Total Glycated Haemoglobinmentioning
confidence: 99%
“…In case-control studies including French subjects selected from a population-based registry of births 33,34 , individuals born SGA demonstrated hyperinsulinemia and insulin resistance as early as the age of 20 years when compared with controls born with normal size. In a recent German study, lower birth weight was associated with higher HbA1c among healthy non-diabetic youth 35,36 . Exposure to maternal DM Several reports have convincingly shown that exposure to maternal DM in utero isa significant risk factor for obesity, IGT, and Type 2DM in youth 37 .…”
Section: Psychosocial Factorsmentioning
confidence: 92%